Access control method of laboratory cloud data based on internet of things technology. (15th March 2023) - Wang, Liuyang; Yu, Yangxin
In order to solve the problems of low access efficiency and poor security in the access control method of laboratory cloud data in the environment of internet of things, this paper proposes the access control method of laboratory cloud data based on internet of things technology. It decomposes the data in the laboratory cloud database into the minimum attributes, encrypts the attributes of the acquired laboratory cloud data, and generates the minimum granularity key that meets the access tree constraints. It combines the internet of things technology and proxy re encryption technology, maps the access structure and attribute set through hash function, encrypts the symmetric key with CP-ABE scheme, and realises the number of laboratory clouds According to the access control method. The simulation results show that the minimum memory cost of the proposed method is 524 bytes, and the highest efficiency is about 98%.